2023
DOI: 10.1177/20503121231152763
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction during the COVID-19 pandemic among adolescents in southeast Nigeria and implications for adolescent care in the post-pandemic era: A cross-sectional study

Abstract: Objectives: This study aimed to determine the prevalence and associated factors of internet addiction amongst adolescents in Southeast Nigeria during the coronavirus disease 2019 (COVID-19) era. Methods: A cross-sectional study was carried out in 10 randomly selected secondary schools, 2 (one urban and one rural) each from Abia, Anambra, Ebonyi Enugu and Imo states of southeastern Nigeria between July and August 2021. Data on demographic variables were collected using a structured self-administered questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Future research on dopamine interactions, from the molecular, cellular, and integrative brain circuitry levels, and their underlying behaviors has acquired a novel global significance in this new mental health context [ 89 , 143 , 146 ]. This paper prompts further investigations into the still underexplored links between dopamine-mediated reward functions, serotonin functions, inflammatory responses, hormonal functions, and their implications for pathological brain adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research on dopamine interactions, from the molecular, cellular, and integrative brain circuitry levels, and their underlying behaviors has acquired a novel global significance in this new mental health context [ 89 , 143 , 146 ]. This paper prompts further investigations into the still underexplored links between dopamine-mediated reward functions, serotonin functions, inflammatory responses, hormonal functions, and their implications for pathological brain adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Interdependent variables such as sociocultural factors, biological vulnerabilities (genetic predisposition and preexisting metabolic disorders), and psychological factors (personality characteristics and a negative affect) play a critical role [ 135 , 136 , 137 , 138 , 139 , 140 ]. Excessive seeking of the new digital drug and addiction to the internet have been identified as part of the consequences of the COVID-19 pandemic, with a major impact on the mental health of predominantly young people and teenagers [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. This involves, like all compulsive behavior loops, the brain’s reward circuitry, with all the complex interactions between environmental, metabolic, and neurobiological changes in the brain discussed above.…”
Section: Covid-19 Pandemic and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“… Gavurova et al (2022) revealed significant gender difference in IA among Slovak college students ( N = 1,677), with males showing higher levels of overall IA and its subdomains including neglect of work and social life, and lack of control. Similarly, compared to female secondary school students in Nigeria, males showed a roughly 2-fold higher likelihood of being Internet addicted (N = 851; Onukwuli et al, 2023 ). These findings are consistent with research prior to the pandemic indicating higher rates of IA among male students ( Liang et al, 2016 ; Vigna-Taglianti et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…Regarding gender differences in IA, the basic picture is that men have significantly higher rates of IA than women ( Anand et al, 2018 ; Onukwuli et al, 2023 ), although there are minor exceptions ( Yang et al, 2021 ). Obviously, it is important to ask whether gender would interact with other factors to shape IA.…”
Section: Introductionmentioning
confidence: 99%